Recycling & redesigning logos a designer's guide to refreshing & rethinking design - Hodgson, Michael (Michael R.) (Rockport Publishers, 2010)
This title demonstrates the strategies and processes of successful redesigns and shows readers how to build on the equity the brand already retains to create a fresh look. The case studies feature before and afters of the logos and discuss why the redesign was necessary.